Surface treatment of interfacial properties of Shape Memory Alloy composites. (May 2015) - Xu, L. D.; Sun, X. Y.; Wan, P.; Sun, X. D.; Wang, Z. Q.
<x content-type="archive" xml:space="preserve">Abstract</x> The main reasons of restrictions shape memory alloy application and development are weak interfacial bonding strength between Shape Memory Alloy (SMA) fibres and matrix materials. In this paper, the interfacial properties of SMA composites are studied by the combination of theoretical analysis and experimental methods.1 Surface treatment of SMA fibres on the three methods is used to improve the surface roughness to increase the interfacial bond strength between SMAs and matrix materials.